Hidrox® and Endometriosis: Biochemical Evaluation of Oxidative Stress and Pain - Marika Cordaro; Angela Trovato Salinaro; Rosalba Siracusa; Ramona D'Amico; Daniela Impellizzeri; Maria Scuto; Maria Laura Ontario; Livia Interdonato; Roberto Crea; Roberta Fusco; Salvatore Cuzzocrea; Rosanna Di Paola; et al. (MDPI AG, 2021)
Endometriosis is a gynecological and painful condition affecting women of reproductive age. It is characterized by dysfunctional endometrium-like implants outside of the uterine cavity. The purpose of this study was to evaluate the effects of Hidrox®, an aqueous extract of olive pulp containing hydroxytyrosol, on endometriotic lesions associated with pro-oxidative alterations and pain-like behaviors. Endometriosis was induced by intraperitoneal injection of uterine fragments, and Hidrox® was administered daily. At the end of the 14-day treatment, behavioral alterations were assessed and hippocampal tissues were collected. Laparotomy was performed, and the endometrial implants were harvested for histological and biochemical analysis. Hidrox® treatment reduced endometriotic implant area, diameter and volumes. Vehicle-treated rats showed lesional fibrosis, epithelial-mesenchymal transition and fibroblast-myofibroblast transdifferentiation, angiogenesis and pro-oxidative alterations in the peritoneal cavity. Hidrox® treatment reduced the aniline blue-stained area, α-smooth muscle actin (α-sma) and CD34 positive expressions. Moreover, it reduced mast cell recruitment into the lesions, myeloperoxidase activity and lipid peroxidation and increased superoxide dismutase (SOD) activity and glutathione levels in the endometrial explants. In the peritoneal fluid, Hidrox® treatment reduced interleukin (IL)-1β, IL2, IL6, tumor necrosis factor-α (TNF-α) and vascular endothelial grow factor (VEGF) levels increased by the disease. Hidrox® administration also reduced peripheral and visceral sensibility as shown by the behavioral tests (open field test, hot plate test, elevated plus maze test and acetic-acid-induced abdominal contractions). Animals treated with Hidrox® also showed reduced blood-brain barrier permeability and mast cell infiltration in the hippocampus, as well as astrocyte and microglia activation and brain oxidative status restoring brain-derived neurotrophic factor (BDNF) protein expression and increasing Nuclear factor erythroid 2-related factor 2 (Nfr2) nuclear translocation. In conclusion, Hidrox® displayed potential ameliorative effects on endometriotic implants and related pain-induced behaviors due to its potent antioxidative properties.